MOLECULAR AND PHENOTYPIC CHARACTERIZATION OF ROMANIAN WINTER WHEAT (TRITICUM AESTIVUM L.) LINES IN CONTEXT OF PRE-HARVEST SPROUTING - Eszter Vas (Agricultura, 2014)
The main aims of our study are the genotypic and phenotypic analysis of four Romanian wheat (Triticum aestivum) lines. The results will be used in further breeding studies for increasing the pre-harvest sprouting (PHS) resistance in wheat. PHS occurs when the germination of the seed on the spike starts in the field before harvest because of high humidity and weather conditions. This damage causes economic and yield losses all over the world. The four investigated parental lines, with different sensibility to PHS, were Turda 95 (sensible), Turda 18-94 (resistant), Lovrin 32 (sensible), Fundulea 29 (resistant). The molecular study was performed with 640 SSR markers. The results showed that between Turda 95 and Turda 18-94 line 90 primers were polymorphic (14%), between Turda 95 and Fundulea 29 line 75 primers were polymorphic (11.17%) and between Turda 18-94 and Fundulea 29 line 83 primers were polymorphic (12.97%). The result from the phenotypic characterization of heading date and plant height showed that the F2 population of the cross Turda 95 and Turda 18-94 has normal distribution, and the PHS scoring shows bimodal distribution and these data can be used for next analysis.